ECOLOGICALLY SUSTAINABLE DESIGN: ENVIRONMENTAL PRESERVATION AND ENERGY SAVING (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In an era where climate change, resource depletion, and environmental degradation have become global concerns, ecologically sustainable design has emerged as a critical solution to mitigate these issues. This design philosophy focuses on creating buildings, products, and systems that are environmentally responsible and resource-efficient throughout their life cycle — from planning and construction to operation, maintenance, and eventual disposal. The two core goals of this approach are environmental preservation and energy saving